Convergence of the Salience of Terrorism in the European Union Before and After Terrorist Attacks - De Roy van Zuijdewijn, Jeanine (Terrorism and political violence, 2021)
Many European countries have been the target of jihadist terrorist attacks between 2015 and 2017. While the chance of becoming a victim of a terrorist attack is low, terrorism scholars have emphasized that terrorism does not revolve around statistics and casualty numbers. Terrorists use attacks to reach an audience and affect groups beyond the direct victims. To this date, little is known about how terrorist attacks might affect the salience of terrorism beyond national borders. This paper investigates possible convergence of issue salience of terrorism among citizens within the European Union for ten jihadist attacks in the period 2015–2017 using Eurobarometer survey data. The results indicate that it is not simply a question of convergence or divergence of salience of terrorism after a terrorist attack. The connection is multidirectional and depending upon a variety of factors. Most importantly, we observed convergence on the EU-level, but divergence on the national level. This raises important questions about the transnationality of the effects of terrorism. As this research does not test nor find a causal mechanism and is solely dependent on existing data, further research is necessary to test some of its findings.